2007
DOI: 10.1007/s00040-007-0923-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying division of labor: borrowing tools from sociology, sociobiology, information theory, landscape ecology, and biogeography

Abstract: How do we quantify division of labor? We review several fields (sociology, landscape ecology, statistics, information theory, and biogeography) that have been cognizant of these questions and been somewhat successful at answering them. We review fourteen indices for quantifying division of labor, sensu lato, which can be categorized into four families: Shannons index/entropy, Simpsons index, geometric mean, and standard/absolute deviation (including coefficients of variation). We argue that those indices using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…We replicated each treatment 50 times and used Shannon mutual information [as proposed by Gorelick et al (27); see Materials and Methods] to measure the amount of division of labor that evolved within the colonies. Table 2 summarizes our results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We replicated each treatment 50 times and used Shannon mutual information [as proposed by Gorelick et al (27); see Materials and Methods] to measure the amount of division of labor that evolved within the colonies. Table 2 summarizes our results.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the amount of division of labor present within a colony, we use Shannon mutual information as proposed by Gorelick et al (27). Shannon mutual information is defined as: IðN; MÞ = X i ∈ N; j ∈ M p ij * ln p ij p i * p j where i is an organism, N is the set of organisms that performed a task within the colony, j is a type of task, and M is the set of types of tasks.…”
Section: Methodsmentioning
confidence: 99%
“…DOL was quantified using the index established in Gorelick et al (2004); for updated definitions see also Gorelick and Bertram 2007;Dornhaus et al 2009). …”
Section: Statistical Analysesmentioning
confidence: 99%
“…In social insects, network models generally treat the workers as nodes, which are connected to each other via communicative interactions (edges), although Fewell (2003) recently suggested that tasks can also be treated as nodes (also see Gorelick and Bertram, 2007). Previous network models of task allocation have assessed how a colonys workers can be effectively distributed among several different tasks.…”
Section: Introductionmentioning
confidence: 99%